Highly Effective Crosslinker for Redox-Sensitive Gene Carriers - Lin Lin; Jie Chen; Yingying Hu; Huapan Fang; Kui Wang; Huayu Tian; Xuesi Chen (Advances in Polymer Technology)
Polyethyleneimine (PEI) has been extensively used as a common gene carrier due to its high gene transfection efficiency. PEI1.8k shows significantly lower cytotoxicity than its high molecular weight counterparts. However, it also has the problem of low gene transfection efficiency. To address the dilemma, a highly effective crosslinker (DTME) was synthesized to react with PEI1.8k to obtain CS-PEI1.8k. The reaction showed several advantages, such as a fast process in room temperature within nine hours with the product which can directly complex with DNA after removing the solvent. The ability of CS-PEI1.8k to agglomerate with DNA was proven by particle size, zeta potential, and gel retardation assays. The cytotoxic in vitro transfection ability and cell internalization capacity of CS-PEI1.8k were tested to verify the transfection capacity of CS-PEI1.8k. Moreover, we also studied the mechanism of the relatively high level of gene transfection by this binary complex compared with PEI25k.